Digital Libraries for Open Knowledge: 23rd International Conference on Theory and Practice of Digital Libraries, TPDL 2019, Oslo, Norway, September 9-12, 2019, Proceedings - International Conference on Theory and Practice of Digital Libraries (TPDL); Doucet, Antoine (Lecture Notes in Computer Science (11799), 2019)
This book constitutes the proceedings of the 23rd International Conference on Theory and Practice of Digital Libraries, TPDL 2019, held in Olslo, Norway, in September 2019. The 16 revised full papers,12 short papers and 18 poster papers presented were carefully reviewed and selected from 75 submissions. The general theme of TPDL 2019 was Connecting with Communities and so the papers attempt to facilitate establishing connections and convergences between diverse research communities such as Digital Humanities, Information Sciences and others that could benefit from ecosystems offered by digital libraries and repositories. To become especially useful to the diverse research and practitioner communities digital libraries need to consider special needs and requirements for effective data utilization, management and exploitation.